Factors associated with previous quit attempts and motivation to quit, amongst primary care patients who are current smokers in Macedonia: a Breathe Well study - Stanoevski, Gjorgji; Jordan, Rachel; Adab, Peymanne; Enocson, Alexandra; Stavrikj, Katarina; Ristovska, Radmila; Gjorgjievski, Dragan; Stamenova, Aleksandra; Krstevska, Emilija; Adams, Rachel; Dickens, Andrew; Sitch, Alice; et al. (Centar of Family Medicine, Faculty of Medicine, “Ss. Cyril and Methodius“ University in Skopje, 2021)
Aim To explore the association between level of nicotine dependence and previous quit attempts and motivation to quit smoking amongst primary care patients. Method We analysed baseline questionnaire data from a randomized controlled trial of a smoking cessation intervention in 31 primary care practices in North Macedonia. Participants were aged ≥35 years and smoked >10 cigarettes/day. Regression models assessed associations between nicotine dependence (Fagerstrom) and intention to quit and previous attempts to quit, adjusting for sociodemographic variables. Results Data was available for 1328 patients. Participants had a mean age of 51,2 (SD 10,3) years, reported a mean smoking history of 39,3 (SD 22,7) pack years and 51% (n=679) were female. 83% (n=1100) of participants were of Macedonian ethnicity. 702 participants (52.9%) reported either moderate or high nicotine dependence. Approximately half of the participants (707/1328, 53.2%, reported previous serious quit attempts, with the majority of these (565/707, 79.9%) reporting 1-3 attempts. Regarding current motivation for quitting, the majority (69.2%) wanted to quit, and 78 (6%) intended to quit in the next 1-3 months. Participants with high nicotine dependence were less likely to have made previous quit attempts (OR=0.90; 95%CI 0.85 to 0.95). Nicotine dependency showed no significant association with current intention to quit (OR=1.00; 95% CI 0.90 to 1.12). Conclusion We found that the majority of smokers want to quit, but those with higher nicotine dependency were less likely to have made previous quit attempts. Declaration of Interest (including funding source and trial registration as appropriate) The authors declare no conflicts of interest. The NIHR Global Health Research (GHR) Programme is funded through UK Official Development Assistance (ODA) via the Department of Health and Social Care (DHSC). The views expressed in this publication are those of the author(s) and not necessarily those of the NIHR or the Department of Health and Social Care. We gratefully acknowledge IPCRG for introducing us to the primary care networks involved in this study and for its continued facilitation of clinical engagement. The study is registered at http://www.isrctn.com(ISRCTN54228638)
Keywords: BreatheWell; Exhaled CO; lung age; primary care; smoking cessation; VBA